Rafflesia arnoldii Motif with Kaganga Letter in Besurek Batik for Women's Ready-to-Wear Fashion Collections - Devina Nathania; Dewi Isma Aryani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
Besurek Batik from Bengkulu, which has been resurrected in the modern period after a break dating back to 1600, served as the primary inspiration for the design of the INSCRIBED ready-to-wear collection for ladies. Besurek Batik contains key components, such as the Rafflesia arnoldii flower pattern and the Kaganga letter, which is unique to Bengkulu. The two components are then modernized through a combination of fabrics, material design, color combinations, and ready-to-wear morphologies for women, allowing them to exhibit current batik in a more appealing, modern, and acceptable manner to the urban community. The design details included the use of taffeta and organza fabrics, the application of material design in the form of a combination of color dipping techniques in cold and hot water, gutta resist painting for making the motifs also being the main dye, and French knott embroidery techniques. The combination of these techniques was poured into the INSCRIBED collection, which is ready-to-wear clothing for women aged 20-35 years old with modern, feminine, smart characters, and respect for local culture who live in urban Indonesia. The INSCRIBED collection as a whole is able to produce a traditional yet modern impression that is in line with the times and has high aesthetic value, this involves exploring how the collection successfully blends traditional elements of Besurek batik with Rafflesia arnoldii flower pattern and Kaganga letters to contemporary fashion design. The goal is to show how this fusion not only preserves cultural heritage but also makes it relevant and appealing to modern urban audiences. The PBL (Project Based Learning) technique is used to achieve final results by learning through real-world projects, including information search and data synthesis, material investigation, feasibility assessment, and design interpretation.